2018
DOI: 10.1002/dev.21797
|View full text |Cite
|
Sign up to set email alerts
|

Visual preferences for direct‐gaze faces in infant macaques (Macaca mulatta) with limited face exposure

Abstract: From birth, human and nonhuman primates attend more to faces with direct gaze compared with averted gaze, and previous studies report that attention to the eyes is linked to the emergence of later social skills. Here, we explored whether early experiences influence attraction to eye contact in infant macaques by examining their attention to face pairs varying in their gaze direction across the first 13 weeks of life. Infants raised by human caretakers had limited conspecific interactions (nursery‐reared; N = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 77 publications
(99 reference statements)
2
9
0
Order By: Relevance
“…These findings are aligned with previous research in human infants that reported early social preferences and growing social attention with age (Bahrick, Krogh‐Jespersen, Argumosa & Lopez, 2014; Frank et al., 2009, 2014; Pierce et al., 2011; Reid et al., 2017; Valenza et al., 1996). Our results are also consistent with prior longitudinal studies in macaque infants that found early sensitivity to eye‐contact, and age‐related increases in looking to faces and the eyes across the first 3 months after birth (Muschinski et al., 2016; Simpson et al., 2017; Simpson, Paukner, Pedersen, Ferrari, & Parr, 2019). While the aforementioned studies did not have a dynamic nonsocial control condition, such studies reported that both human and monkey infants displayed increasing looking times to conspecific faces with age.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are aligned with previous research in human infants that reported early social preferences and growing social attention with age (Bahrick, Krogh‐Jespersen, Argumosa & Lopez, 2014; Frank et al., 2009, 2014; Pierce et al., 2011; Reid et al., 2017; Valenza et al., 1996). Our results are also consistent with prior longitudinal studies in macaque infants that found early sensitivity to eye‐contact, and age‐related increases in looking to faces and the eyes across the first 3 months after birth (Muschinski et al., 2016; Simpson et al., 2017; Simpson, Paukner, Pedersen, Ferrari, & Parr, 2019). While the aforementioned studies did not have a dynamic nonsocial control condition, such studies reported that both human and monkey infants displayed increasing looking times to conspecific faces with age.…”
Section: Discussionsupporting
confidence: 92%
“…Studies in nonhuman primates offer converging evidence of the malleability of infants' sensitivity to gaze direction. Infant monkeys reared in richer social environments attend more to direct gaze faces compared to averted gaze faces (Muschinski et al, ; Simpson, Paukner, Pedersen, Ferrari, & Parr, ).…”
Section: Discussionmentioning
confidence: 99%
“…Infant monkeys reared in richer social environments attend more to direct gaze faces compared to averted gaze faces (Muschinski et al, 2016;Simpson, Paukner, Pedersen, Ferrari, & Parr, 2018).…”
Section: Age Differences In Own-species Bias and The Role Of Experimentioning
confidence: 99%
“…Nursery-reared macaques (i.e. raised in a nursery since birth) have limited early social experience and are at increased risk for maladaptive social outcomes, including increased stress reactivity ( Dettmer et al, 2012 ) and socio-emotional difficulties from the earliest months of life (e.g., Paukner et al, 2020 ; Simpson et al, 2019 , 2016 ; Vanderwert et al, 2015 ). Such deficits can be predictive of longer-term negative outcomes, such as an increased risk for anxiety ( Conti et al, 2012 ; Dettmer and Suomi, 2014 ).…”
Section: Introductionmentioning
confidence: 99%